1991
DOI: 10.6028/nist.ir.4514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the state-of-the-art for process monitoring sensors for polymer composites

Abstract: A variety of techniques have been applied to monitoring the changes that occur in the resin during composite processing. This report identifies and analyzes those techniques that have the most promise for on-line application, namely: ultrasonic, dielectric, spectroscopic, and optical techniques. All these methods have advantages and disadvantages, and the best technique for a given application will depend strongly on the materials and processes involved. This report discusses these on-line monitoring technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 83 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…Other specialty fibres such as optical fibres are currently being investigated for structural health monitoring applications10,11. Fig.…”
Section: Frp Materials and Test Methodsmentioning
confidence: 99%
“…Other specialty fibres such as optical fibres are currently being investigated for structural health monitoring applications10,11. Fig.…”
Section: Frp Materials and Test Methodsmentioning
confidence: 99%
“…The final properties of a fiber reinforced composite depend on the fiber properties and architecture, the extent of resin cure and resultant matrix properties, the quality of the mold filling, and the properties of the fiber/resin interface (2,3). In general, it is poorly understood how processing conditions will influence these factors, so process optimization is largely determined by expensive and time consuming empirical techniques (4). To complicate matters, batch-to-batch variations of fiber and resin quality make reproducibility difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the key to high performance is the cure monitoring and optimization of the manufacturing process (1). An intelligent manufacturing process has to be able to recognize the features of the process by using in-situ sensors and then to activate the controller connected with the system actuators.…”
Section: Introductionmentioning
confidence: 99%